Pengaruh Profitabilitas, Leverage dan Firm Size terhadap Cash Holding pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia (BEI) Tahun 2017-2019 - Intan Novia Astuti; Sisca Mediyanti; Ainul Ridha; Eliana Eliana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIES Banda Aceh, 2021)
This study aims to determine the effect profitability, leverage and firm size on Cash Holding on Banking Companies listed on the Indonesia Stock Exchange in 2017-2019. The population in this study are Banking Companies listed on the Indonesia Stock Exchange in 2017-2019 obtained 45 companies. The sampling method used is purposive sampling method and obtained 25 companies are meet the criteria and 75 data observation are obtained. Data analysis method used is multiple linear regression analysis. The result showed that simultaneous profitability, leverage and firm size effect cash holding. Partially, profitability and leverage effect cash holdings. While firm size has no effect on cash holding.